Mekanisme Adaptasi Jagung terhadap Cekaman NaCl: Pola Serapan Anion dan Kation - Utama, Muhammad Zulman Harja; Haryoko, Widodo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Salt solubility is the abiotic pressure which has the most effect on the loss of plant quantity and quality. Salinity not only makes plants stressful but also presents severe constraints on crop production so an attempt to understand plant adaptation mechanisms is important for expanding agricultural production on saline soils. This study aimed to obtain a mechanism for the adaptation of hybrid and composites maize to NaCl stress through anion and cation absorption patterns. The experiments were carried out at the LLDikti Region X Laboratory from May to August 2016. The experiments were arranged in a factorial complete randomized design with three replications. The first factor was corn varieties, namely: hybrid corn (Pioneer 22 and Bisi 12), and composite corn (Bisma and Sukmaraga). The second factor was level of NaCl, namely: 0.0 mg kg-1 NaCl pH 5.0, and 4,000 mg kg-1 NaCl pH 5.0. Measurement of anions and cations using Spectroquant Thermoreator TR Nova 420. The adaptability of hybrid maize and composites to NaCl stress occurred through the mechanism of anion absorption and cation metabolism. The difference in the percentage of NO3-, NO2-, PO4-, NH4+, and K+ levels between hybrid maize varieties and composites showed a difference in the adaptation ability of maize varieties to salinity stress. Keywords: abiotic, mechanism, salinity, varieties